Developing Mathematics Learning Strategy Module Based on Journal Review - Kusumawati, Ratih; Nayazik, Akhmad (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
Pre-service teachers need to know the variety of learning methods and they should have the ability to plan learning strategies as well. This study aims to develop a module of mathematics learning strategy based on the review of articles published from 2014–2018. This study was conducted using Borg and Gall development model and the quality criteria used referred to Nieveen (valid, practical, and effective). The result shows that the module has met the validity criteria of 3.4, practical criteria of 82%, and it also has fulfilled the criteria of effectiveness. This module is recommended as a reference to study about recent mathematics learning strategy. A further study is needed to develop such a module based on international journals.